An Empirical Study on the Influence of the Basic Medical Insurance for Urban and Rural Residents on Family Financial Asset Allocation - Li, Shenglin; Yang, Yifei (Frontiers in Public Health, 2021)
This paper empirically examined whether participation in the Basic Medical Insurance for Urban and Rural Residents impacted families' allocation to risk assets and risk-free assets using the Heckman two-step method, which is based on the China Household Finance Survey micro data of 2013, 2015, and 2017. The results showed that participation in the Basic Medical Insurance for Urban and Rural Residents can promote families' reasonable choice between risk assets and risk-free assets to a certain extent. To be specific, the risk asset investments are squeezed out for the originally risk-seeking families, while the risk-free asset investments are squeezed out for the originally risk-adverse families. We tested the robustness of the benchmark model and the mediating effect model with different definitions of risk assets and risk-free assets. Also, the analysis of the mechanism showed that this increases families' risk perception—turning their risk attitude more cautious and their investment attitude more rational. To further consolidate the social security attributes of the Basic Medical Insurance for Urban and Rural Residents, behind its high coverage, we should also pay attention to its influence on the investment preferences of families with different social and economic statuses, thereby giving full play to its role in promoting the development of China's financial market. In future research, we can also try to use measurement models such as PSM-DID models, and find the connections and progressive relations between different models, in order to obtain the inquiry results of different dimensions. For the direction of further research in the future, we believe that can be used to test whether the conclusion whose data configuration of the basic medical insurance for family financial assets choice influence is a universal in developing countries, to explore the developing countries to promote the health security system for the influence of its national household financial asset allocation and the corresponding policy recommendations. JEL Classification: D14, G11, H55, I18.